2019
DOI: 10.1111/jdi.13000
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 is inversely associated with liver fibrotic markers in patients with type 2 diabetes mellitus

Abstract: Aims/Introduction Insulin‐like growth factor‐1 (IGF‐1) regulates mitochondrial function, oxidative stress, inflammation, stellate cells and insulin sensitivity in the liver, and it might be associated with liver fibrosis from non‐alcoholic steatohepatitis. In contrast, type 2 diabetes mellitus is closely associated with the progression from non‐alcoholic fatty liver to non‐alcoholic steatohepatitis and cirrhosis, so careful evaluation of liver fibrosis is required for patients with type 2 diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
2
5
0
1
Order By: Relevance
“…Finally, the pattern of IGF-1 mRNA expression between groups was consistent with ones observed in circulating and liver homogenates protein levels. This is in line with the reported literature showing inverse correlation between IGF-1 and fibrosis [55].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the pattern of IGF-1 mRNA expression between groups was consistent with ones observed in circulating and liver homogenates protein levels. This is in line with the reported literature showing inverse correlation between IGF-1 and fibrosis [55].…”
Section: Discussionsupporting
confidence: 93%
“…While a few clinical studies have associated low serum IGF-1 with increased severity of steatosis ( 46 , 47 ) or lobular inflammation ( 48 ), our results and those of others ( 49 ) failed to show any association. On the other hand, clinical studies are consensual when reporting low serum IGF-1 association with the severity of fibrosis ( 46 , 48 50 ). In fact, in vitro and in vivo studies showed that IGF-1 can induce cellular senescence and hepatic stellate cell inactivation through a p53-dependent manner, thus improving experimental fibrosis ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serum IGF-1 levels are decreased in cirrhosis as the synthetic capacity of the liver is diminished [ 18 , 19 ]. Hepatic IGF-1 production is also lower in those with higher degrees of steatosis, non-alcoholic fatty liver disease (NAFLD) activity score (NAS), and hepatic fibrosis [ 20 , 21 ]. Conversely, NAFLD occurs more commonly in adult GHD.…”
Section: The Liver As An Endocrine Organmentioning
confidence: 99%